1987
DOI: 10.1085/jgp.89.3.481
|View full text |Cite
|
Sign up to set email alerts
|

Na+- and cGMP-induced Ca2+ fluxes in frog rod photoreceptors.

Abstract: We have examined the Cal ' content and pathways of Ca l ' transport in frog rod outer segments using the Ca"-indicating dye arsenazo III . The experiments employed suspensions of outer segments of truncated, but physiologically functional, frog rods (OS-IS), intact isolated outer segments (intact OS), and leaky outer segments (leaky OS with a plasma membrane leaky to small solutes, but with sealed disk membranes). We observed the following . (a) Intact OS or OS-IS isolated and purified in Percoll-Ringer's solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 37 publications
4
13
0
Order By: Relevance
“…3) demonstrate that when [Ca2+]0 is substituted for Ba2+, the slow tails are significantly reduced in magnitude and their decay time is slowed, consistent with a reduced capacity of the exchanger. As expected from previous work in the visual system and in heart (Tibbits & Philipson, 1982;Kimura et al 1987 (Baker & McNaughton, 1976;Yau & Nakatani, 1984;Schnetkamp & Bownds, 1987) suggest that this manoeuvre should inhibit the Na+-Ca2+ exchanger. Our data (Fig.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…3) demonstrate that when [Ca2+]0 is substituted for Ba2+, the slow tails are significantly reduced in magnitude and their decay time is slowed, consistent with a reduced capacity of the exchanger. As expected from previous work in the visual system and in heart (Tibbits & Philipson, 1982;Kimura et al 1987 (Baker & McNaughton, 1976;Yau & Nakatani, 1984;Schnetkamp & Bownds, 1987) suggest that this manoeuvre should inhibit the Na+-Ca2+ exchanger. Our data (Fig.…”
Section: Discussionsupporting
confidence: 75%
“…In the squid axon (Baker & McNaughton, 1976) and in amphibian retina (Yau & Nakatani, 1984;Schnetkamp & Bownds, 1987), fluxes mediated by the Na+-Ca2+ exchanger and currents attributed to its activity can be inhibited by raising [K+]o. Consistent with this we have observed (n = 8) that the slow tail currents were reduced substantially by raising…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracellular Ca 2+ buffers and sensors are thought to bind as much as 99% of Ca 2+ which enters the cell through CNG channels (47,51). Their action seems to be essential for cell survival, because mutations in genes encoding different photoreceptor Ca 2+ -binding proteins are linked to several human pathologies leading to blindness (52) In addition to plasma membrane Ca 2+ influx and extrusion, [Ca 2+ ]i in the OS may also be regulated by Ca 2+ release and uptake from internal compartments, such as the stack of disks which fill the rod OS (54)(55)(56)(57). Early studies suggested that the disks can accumulate significant amounts of Ca 2+ .…”
Section: Ca 2+ Extrusion and Buffering In The Outer Segmentmentioning
confidence: 99%
“…The light-sensitive conductance of rods is a cGMP-dependent conductance (Fesenko, Kolesnikov & Lynbarsky, 1985;Yau & Nakatani, 1985;Zimmerman et al, 1985;Matthews, 1987), which can pass a current of Ca 2+ (Capovilla et al, 1983;Yau & Nakatani, 1984b;Hodgkin et al, 1985). The second pathway for Ca 2+ transport is Na-Ca exchange (Schnetkamp, 1980;Yau & Nakatani, 1984b;Schnetkamp, 1986;Hodgkin, McNaughton & Nunn, 1987;Schnetkamp & Bownds, 1987). Both pathways have a considerable capacity and can change total intracellular Ca 2 § by as much as 0.1 (amphibian rods) -0.5 (bovine rods) mM/sec.…”
Section: Introductionmentioning
confidence: 99%